Association between the cardiometabolic index and osteoporosis: a cross-sectional study of the NHANES - Li, Deyan; Li, Jinli; Li, Yijun; Dong, Wei; Lin, Zhuofeng (Frontiers in Public Health, 2024)
Background The cardiometabolic index (CMI) is a novel metabolic biomarker, but research on its association with osteoporosis (OP) is limited. The objective of this research was to clarify the relationship between CMI and OP in the senior population of the United States. Methods This study conducted a cross-sectional analysis using NHANES data 2007 - 2018 with exclusion of 2011-2012 and 2015-2016 cycles. Logistic regression was used to investigate the relationship between CMI and OP prevalence. Restricted cubic spline curve (RCS) and threshold saturation analyses were performed to explore the nonlinear association between CMI and OP prevalence. Subgroup analyses, sensitivity analyses, and additional analyses were conducted to ensure the robustness and reliability of the findings. Results The study included 4191 participants, revealing that those with OP had significantly lower CMI levels. Logistic regression revealed a strong inverse correlation between Log CMI and OP (OR=0.72, 95% CI=0.59-0.88), which persisted after adjusting for covariates. RCS analysis revealed a nonlinear inverse relationship with the critical threshold at CMI = 0.93. Below this threshold, each unit increase in CMI was associated with a 37% reduction in OP prevalence, but changes above this threshold were not significant. Subgroup and sensitivity analyses confirmed the robustness of the findings. Conclusion Elevated CMI exhibited a robust inverse correlation with the prevalence of OP in the elderly U.S. population. Maintaining a moderate CMI significantly diminishes the risk of developing OP.